Trends in healthy life expectancy among older Brazilian women between 1998 and 2008 - Nepomuceno, Marília Regina; Turra, Cássio Maldonado (Revista de Saúde Pública, 2015)
OBJECTIVE To analyze conditional and unconditional healthy life expectancy among older Brazilian women.METHODS This cross-sectional study used the intercensal technique to estimate, in the absence of longitudinal data, healthy life expectancy that is conditional and unconditional on the individual’s current health status. The data used were obtained from the Pesquisa Nacional por Amostra de Domicílios (National Household Sample Survey) of 1998, 2003, and 2008. This sample comprised 11,171; 13,694; and 16,259 women aged 65 years or more, respectively. Complete mortality tables from the Brazilian Institute of Geography and Statistics for the years 2001 and 2006 were also used. The definition of health status was based on the difficulty in performing activities of daily living.RESULTS The remaining lifetime was strongly dependent on the current health status of the older women. Between 1998 and 2003, the amount of time lived with disability for healthy women at age 65 was 9.8%. This percentage increased to 66.2% when the women already presented some disability at age 65. Temporal analysis showed that the active life expectancy of the women at age 65 increased between 1998-2003 (19.3 years) and 2003-2008 (19.4 years). However, life years gained have been mainly focused on the unhealthy state.CONCLUSIONS Analysis of conditional and unconditional life expectancy indicated that live years gained are a result of the decline of mortality in unhealthy states. This pattern suggests that there has been no reduction in morbidity among older women in Brazil between 1998 and 2008.